The Employment Potential of Labor Intensive Industries in India's Organized Manufacturing - Deb Kusum Das; Deepika Wadhwa; Gunajit Kalita (Indian Council for Research on International Economic Relations (ICRIER), 2009)
This paper attempts to identify and examine labor intensive industries in the organized manufacturing sector in India in order to understand their employment generation potential. Using the data from the Annual Survey of Industries (Government of India, various issues), the labor intensity for 97 industries at the 4-digit disaggregate level was computed for the period 1990-91 to 2003-04. The study identifies 31 industries as 'labor intensive industries' within India's organized manufacturing sector. The study finds that labor intensity has declined not only for capital intensive industries but also for labor intensive industries during the selected time period. The increase in output failed to generate enough employment growth resulting in a significant decline in employment elasticity. The paper briefly highlights the plausible factors that could have had an impact on labor intensity as well as on the performance of the organized manufacturing sector over the study period.
Keywords: E24; J24; J31; D24; 330; Labor Intensity; Employment Growth; Labor Productivity; Capital Productivity; Organized Manufacturing; Arbeitsproduktivität; Arbeitskosten; Industrie; Beschäftigungseffekt; Qualifikation; Lohnstruktur; Arbeitsrecht; Indien; Südasien